Space-Time Structure of Auroral Radio Absorption Events Observed with the Imaging Riometer at South Pole - Hargreaves, J. K.; Detrick, D. L.; Rosenberg, T. J. (1990)
An imaging riometer system comprising 49 independent beams has been operating at South Pole station since January, 1988. A study of intense, short-duration events from the pre-midnight sector has defined their typical shape as elliptical, with axial ratio 2.3 oriented along the local L-shell. The space-time evolution shows rapid intensifications of the moving absorption patches. This article is from 'The Effect of the Ionosphere on Radiowave Signals and Systems Performance Based on Ionospheric Effects Symposium Held on 1-3 May 1990' AD-A233 797, p76-81.